Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1080/10245332.2015.1133753
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of new formulas and evaluation of the previous red blood cell indices and formulas in the differentiation between beta thalassemia trait and iron deficiency anemia in the Makkah region

Abstract: The England and Fraser and our new formula 1 are the best formulas in men. The England and Fraser and RDW index are the best formulas in women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 17 publications
1
14
0
Order By: Relevance
“…The RDWI had high YI (81.6%). These results are consistent with the findings of other relevant studies who found that the highest YI was obtained for RDWI 69.2%, 83% and 73.8% respectively[23] [24]…”
supporting
confidence: 93%
See 1 more Smart Citation
“…The RDWI had high YI (81.6%). These results are consistent with the findings of other relevant studies who found that the highest YI was obtained for RDWI 69.2%, 83% and 73.8% respectively[23] [24]…”
supporting
confidence: 93%
“…The highest YI was obtained for MCI (85.9%). The Youden's index considers both sensitivity and specificity and provides an appropriate measure of the overall validity of the index or technique [23]. Matos et al, [6] reported that its sensitivity was 99.3%, Specificity 76.7% and YI was 76.0%, and the evaluation of this index by Arora et al, [22] showed high sensitivity to detect IDA (98.81%), excellent diagnostic accuracy and showing good applicability as screening tool in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the highest YI was obtained for RDWI (83). The YI takes into account both sensitivity and specificity and gives an appropriate measure of the validity of technique 22. In the present study, YI evaluated the discriminating function of the red cell indices and their derived formulae.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past 50 years a substantial number of studies in different populations attempted to evaluate these formulas or even generate and suggest new ones aimed at finding the most reliable indices or formulas with the highest sensitivity and specificity or predictive value [6] , [7] , [8] , [9] . However, none of the many different indices or formulas provided 100% sensitivity and 100% specificity within their target populations nor was one formula superior to another, within or between populations.…”
Section: Introductionmentioning
confidence: 99%